Fraud events in the coolest of neighbourhoods: a case study from Gothenburg, Sweden - Thodelius, Charlotta (Crime, law and social change, 2024)
In the current study credit card frauds are analysed. Concepts are taken from crime pattern theory and place-based criminology. The empirical material originates from the urban nightlife of Gothenburg, Sweden, and combines quantitative and qualitative data from different sources. Instead of focusing on the individual’s specific motives for committing crimes, the study has its interest in how place can play a part in fraud events and be a necessary condition in the crime modus operandi. In the conducted analysis, we can clearly see that place matters in the crime series studied, and that the place was not randomly chosen by the offenders.